Mastoid osteoma: a case report - Subha, Sethu Thakachy; Doi, Mohamad; Kumari, Hemalata (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Mastoid osteoma is a rare benign neoplasm of mesenchymal origin. Osteomas of the temporal bone are infrequent, and these mastoid osteomas are a definite rare occurrence. These tumours can present with cosmetic deformity and sometimes with pain. In this report we describe a patient with mastoid osteoma who presented with cosmetic deformity and experienced retro auricular pain.